The Geoarchaeology of a Terraced Landscape : From Aztec Matlatzinco to Modern Calixtlahuaca - Borejsza, Aleksander, 1974-; Smith, Michael Ernest, 1953-; Frederick, Charles D.; Rodríguez López, Isabel (Archaeologist) (Book collections on Project MUSE., 2021)
"This manuscript uses geoarchaeology and the study of landscapes to look at the agrarian history of a settlement in the Toluca Valley, central Mexico, from prehistoric to historic times. It is based on both survey and excavation data, plus geoarchaeological and archival research. It explores how social circumstance promotes the improvement or degradation of agricultural land prehistorically, then the impact of Spanish colonialism on these agrarian systems, and finally, how the long-term modification of these landscapes impacts the valley in post-colonial times"--